Femtosecond Electron Dynamics in Graphene Nanoribbons – A Nonequilibrium Green Functions Approach Within an Extended Hubbard Model. Issue 7 (8th January 2019) - Joost, Jan‐Philip; Schlünzen, Niclas; Bonitz, Michael
Abstract : A new approach to study the correlated femtosecond electron dynamics in finite graphene clusters, such as nanoribbons, is presented here. The systems are described by an extended Hubbard model that takes into account the overlap of adjacent orbitals and hopping between up to third‐nearest neighbors. The model is solved by the nonequilibrium Green functions approach combined with different self‐energy approximations, including the second‐Born and GW self‐energy, to take into account electronic correlations. The description allows us to predict the correlated nonequilibrium dynamics of excited graphene nanostructures of arbitrary geometry containing up to 100 carbon atoms for up to 25 fs. Abstract : The correct description of the correlated nonequilibrium electron dynamics in finite graphene nanostructures always appeared to be an insurmountable task. Now, the authors present an auspicious approach that describes these nanoclusters within an extended Hubbard model that is solved using nonequilibrium Green functions. The inclusion of correlation effects beyond the mean‐field level proves to be of utmost importance.